Relationship between Upper Extremity Lymphatic Drainage and Sentinel Lymph Nodes in Patients with Breast Cancer. (1st April 2019) - Ma, Xiaokai; Wen, Shishuai; Liu, Baofeng; Li, Dumin; Wang, Xiaolong; Kong, Xiaoli; Ma, Tingting; Jiang, Liyu; Yang, Qifeng
Abstract : Purpose . The purpose of this study was to identify the relationship between upper extremity lymphatics and sentinel lymph nodes (SLNs) in breast cancer patients. Methods . Forty-four patients who underwent axillary reverse mapping (ARM) during axillary lymph node dissection (ALND) with SNL biopsy (SLNB) between February 2017 and October 2017 were investigated. ARM was performed using indocyanine green (ICG) to locate the upper extremity lymphatics; methylene blue dye was injected intradermally for SLN mapping. Results . ARM nodes were found in the ALND fields of all examined patients. The rate of identification of upper extremity lymphatics within the SLNB field was 65.9% (29 of 44). The ARM nodes were involved in metastases arising from primary breast tumors in 7 of the patients (15.9%), while no metastases were detected in pathologic axillary lymph node-negative patients. Lymphatics from the upper extremity drained into the SLNs in 5 of the 44 patients (11.4%); their ARM-detected nodes were found to be in close proximity to the SLNs. Conclusions . The ARM nodes and SLNs are closely related and share lymphatic drainage routes. The ARM procedure using fluorescence imaging is both feasible and, in patients who are SLN negative, oncologically safe. ARM using ICG is therefore effective for identifying and preserving upper extremity lymphatics, and SLNB combined with ARM appears to be a promising surgical refinement for preventing upper extremity lymphoedema. Clinical Trial Registration . This trial is registered with ClinicalTrial.gov:NCT02651142 .